Pregnancy, delivery, and neonatal outcomes among women with spinal cord injury in Sweden 1997–2015: A population‐based cohort study. (28th August 2022) - Khalili, Molly; Berlin, Marie; Pettersson, Karin; Lindgren, Carl; Hultling, Claes; Ekéus, Cecilia
Abstract: Introduction: The aim of this study was to describe the rate of pregnancy in spinal cord injured women in Sweden as well as pregnancy, delivery, and neonatal outcomes. Material and Methods: This study was based on data from the Swedish Medical Birth Register and the National Patient Register. The study population included women with spinal cord injury who gave birth in Sweden during the period 1997 to 2015. The general population was used as reference and included all non‐spinal cord injured patients who gave birth during the same period of time. Results: In the spinal cord injury group, 109 births were identified. Eighty‐nine (82%) of them were among paraplegic women and 20 (18%) were among tetraplegic women. Women with spinal cord injury in our study population had urinary tract infections during pregnancy in five cases (5%) and anemia during pregnancy in nine cases (8%), compared with 0.2% and 4%, respectively, in the general population. Compared with the general population more deliveries were induced in the study population, 18 (17%) in the spinal cord injury group and 12% in the general population. Vaginal delivery was achieved in 52 (48%) of the births with 42 of them (39%) being non‐instrumental and 10 (9%) being instrumental vaginal deliveries. Elective cesarean section rate was 34% ( n = 37). Sixteen infants (15%) were born preterm (gestational week <37). We found an overall low rate of pregnancy and delivery complications. Conclusions: Our results show predominantly favorable outcomes of pregnancy and delivery in women with spinal cord injury as well as their infants. These results are in concordance with previous research. Abstract : Outcomes of pregnancy and delivery in women with SCI and their infants are predominantly favorable. There were marginal discrepancies in adverse outcomes compared to the normal population.